Upaya Perubahan Perilaku Penderita Hipertensi Menghemat Biaya Kesehatan Melalui Sosialisasi Bahaya Katastropik di Wilayah Puskesmas Talang Bakung - Solida, Adila; Amir, Andy; Ena Sari, Rumita (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2023)
The prevalence of hypertension in Jambi City has always increased in the last 5 years, including in the working area of ​​the Talang Bakung Health Center. On the other hand, the costs of treating and treating hypertension that must be borne by the community are relatively high, especially if complications occur and are not covered by insurance, so there is a risk of catastrophic expenses that trigger the fragility of the household economy due to illness. The purpose of the service activity is to provide education and outreach about hypertension and its impact on health costs. The activity was attended by 30 participants with hypertension in the Talang Bakung Health Center area. The core activities include providing education about hypertension and its impact on health costs, socializing catastrophic hazards and socializing various supporting programs from the Government. The results of the activity showed that 80% of the participants experienced a significant increase in knowledge and there was a difference in the participants' knowledge between before and after the PPM activity (p=0.000). It is recommended to the Government and Puskesmas to increase campaign efforts to mobilize the community to adopt a healthy and proactive lifestyle in various health programs that support saving health costs so as to avoid catastrophic expenses.